Mieux comprendre la complexification de l’occupation de l’espace pastoral au Ferlo. Un prérequis pour une bonne gestion des ressources naturelles - Abdou Ka; Arthur Perrotton; Birane Cissé; Deborah Goffner (VertigO, 2021)
In the context of global changes, pastoralism is positioned as a relevant production system in semi-arid areas. However, those ecosystems are particularly vulnerable face to global warming. It is now necessary to preserve them and think up flexible planning and management rules rooted in local socio-ecological realities. This article presents work carried out in the Ferlo (Sylvopastoral Zone), inhabited mainly by Fulani pastoralists. For more than half a century, the Ferlo has been the scene of constant development policies and projects accumulated around the management of pastoral resources and the fight against desertification. We defend the idea that difficulties in solving the socio-ecological challenges of the Ferlo come from project development implemented in this area are based on an obsolete narrative. Based on fieldwork and document analysis, we propose an update of this narrative, describing the socio-ecological transition of the Ferlo from the historical system of the hurum to a contemporary system characterized by great complexity. Throughout the article, we draw attention to the potential consequences of the discrepancy between the Ferlo as perceived by public authorities and development agents on the one hand and how Fulani pastoralists de facto use it.